О реализации в системе Matlab метода последовательных приближений для решения нелинейных интегральных уравнений Фредгольма–Урысона ІІ рода - Мосенцова, Л.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
The article is devoted to realization in computing environment Matlab of method of successive approximations of solving for non-linear integral Urison equations of the second kind.